Ensino de filosofia em Moçambique: Filosofia como Potência para Aprendizagem Significativa - Chambisse, Ernesto Daniel (2006)
This dissertation examines the conditions under which happens Philosophy teaching in ESG II (Grades 11 and 12) in Mozambique, by testing the hypothesis that the way Pilosophy is taught at the moment does not contribute to enhacing its potencial for significant learning in the classroom. The work departs from observations of Philosophy teaching practice carried out by teacher trainees from the Universidade Pedagógica. It was made a revision of specialized and complementary literature and a field research in three selected schools one for pre-testing and the other two for in-depth research. The methodological approach is based on qualitative research in the form of a case study. The results of this research lead to the conclusion that there is a need of urgent changes in the conditions under which Philosophy and other ESG II subjects are taught, such as: precarious working conditions, lack of teachinglearning materials, lack of stimuli for the teachers, excess of rigor in MEC planning. This dissertation demonstrate the potential contributions of Philosophy in enhancing the teaching-learning process in Philosophy and other subjects of the curriculum and it has as a purpose the improvement of teaching, especially of Philosophy teaching in Mozambique